Cervical cancer. A call for reflection - Ana Adelaida Abrahantes Ruiz; Magalys Oliver Cruz; Miryam Magali González González del Pino; Katia Rodríguez Palacios; Oscar Narciso Muñoz Hernández; Adys Castro Berberena (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2019)
Cancer is a major health problem, given the high morbidity and mortality it produces. It is one of nature's most complex processes and is the most complicated in the field of medicine. The purpose of this review is to briefly present useful and updated information on cervical cancer. A total of 25 bibliographic sources were consulted, including articles from scientific journals, and others, which were accessed through the main national and international databases of the Infomed computer network, such as Scielo, Google Scholar, PubMed , among others. It was demonstrated that in Cuba the health system makes significant efforts to reduce death rate due to this cause. The women´s negative attitudes, insufficient information about cytological examination, which is the main pillar for prevention, as well as infection with the human papillomavirus, constitute some factors for the increase in cervical cancer. It is of crucial importance to ensure that all women have a cytological test and increase their perception of risk, to improve prevention.